"My Life in the Hospital": Narratives of Children With a Medical Condition. Issue 1 (3rd February 2021) - Capurso, Michele; di Castelbianco, Federico Bianchi; Di Renzo, Magda
Pediatric hospitalization is a common experience that may increase children's sense of isolation and impinge on their social-emotional wellbeing. Educators and medical practitioners could minimize these negative effects of hospitalization if they were able to listen to the voices of the children and, therefore, better meet their needs. This qualitative study provides an overview of how children with a medical condition actively construct and organize their thoughts and feelings about illness, life in hospital, and relationships. We extrapolated from a collection of children's narratives from a previous more comprehensive study (consisting of 379 narratives from children in 29 public hospitals across Italy, age range 3–14 years). Narratives grouped under the headings "Me and my illness" or "Me and the others" were selected and analyzed using interpretative phenomenological analysis (IPA) to identify the richness and complexity of children's experience. Results showed that children's description of their illness was affected both by cognitive and social factors. For children, the concept of feeling ill or well is not linked only to the fact that they are in hospital for a medical condition; rather, it is influenced by their ability to form relationships with others, play, be active, and feel alive within the hospital environment. Listening to narratives can deepen our understanding of children's illness-related experiences and how they make sense of their situation. A set of practice implications are presented to help health professionals and educators to improve their listening capabilities and better prevent adverse pediatric hospitalization outcomes.